Architectural Photogrammetry in Malaysia: An Experience - Ahmad, Anuar; Yaakub, Ibrahim (Fakulti Ukur dan Harta Tanah, 1996)
In Malaysia, there are many historic buildings and monuments. The government realise that the historic buildings and monuments need to be conserved and restored. For this purpose, the National Museum was given the responsibility to record all the historic buildings and monuments. Architectural photogrammetry is one of the method that can be used for recording. It has been used by many countries in the world. However, this method has been used recently in Malaysia. This paper reports an architectural photogrammetry work that has been carried out to produce line drawing of the main entrance facade of the Eastern & Oriental Hotel, Penang. In this work, the photographs were taken using metric camera Wild P32 and the line drawing was produced using an analytical plotter.